The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1515/znc-2007-3-415
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Effect on Constituents of Azolla caroliniana

Abstract: Changes in growth and ultrastructure of Azolla caroliniana in response to elevated UV-B radiation were investigated. Exposure of plants to UV-B radiation for 1, 8, 16, 24 and 48 h exhibited a significant decrease in biomass and relative growth rate. This decrease resulted in an increase in doubling time over the control. Also, Chl a and b contents were significantly decreased especially after 16 h. The reduction was accompanied by a decrease in 5-aminolaevulinic acid content (precursor of chlorophyll). On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Rack height, lamp spacing and lamp power were adjusted as described by Ibrahim and Mostafa (2007) . Plants were rotated under the lamp banks to minimize potential effects resulting from microenvironment variations for 6 h. Samples were taken for chemical analyses.…”
Section: Selenium Treatment and Growth Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rack height, lamp spacing and lamp power were adjusted as described by Ibrahim and Mostafa (2007) . Plants were rotated under the lamp banks to minimize potential effects resulting from microenvironment variations for 6 h. Samples were taken for chemical analyses.…”
Section: Selenium Treatment and Growth Estimationmentioning
confidence: 99%
“…Ultraviolet radiation also produces oxidative stress that arises from the deleterious effects of active oxygen species (Costa et al 2002;Ibrahim and Mostafa 2007) that react with lipids, pigments, proteins and nucleic acid (Dai et al 1997;Nasibi and M-Kalantari 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that, the vegetative growth, the photosynthetic pigments in addition to the UV-absorbing compounds such as phenolics, flavonoids and anthocyanins in Azolla caroliniana were strongly affected by the duration of exposure to UV-B radiation (Ibrahim and Mostafa, 2007). In this study, changes in reservation non-enzymatic antioxidant metabolites and ultrastructure of chloroplast were investigated in relation to UV damage in the aquatic fern Azolla caroliniana.…”
Section: Introductionmentioning
confidence: 93%
“…Plants have evolved mechanisms to avoid and repair UV radiation oxidative stress damage, and the free radicals caused by UV tend to be involved in the induction of antioxidant defense system. In previous studies, it has been concluded that plant growth and biomass accumulation could result from complex interactions between harmful direct and indirect effects of UV and a series of counteracting repair mechanisms (Lesser et al, 1994 andMostafa, 2007). It has been shown that the composition of the aquatic fern Azolla varies profoundly according to environmental conditions and the species (Lumpkin and Plucknett, 2008;Van Hove, 1987 andVan Hove, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation